(untitled) (Altre Modernità, 2012)
In W.H. Hudson’s Green Mansions (1904) the mysterious and enchanting quality of the natural world is represented through the writer’s powerful imagination, and the exotic landscape of the South American rainforest is related to British territorial expansion: according to a long-standing literary tradition, the European colonial desire is projected onto remote, unknown places. On the one hand, the pristine forest appears a pure space, a site unspoiled by colonial expansion, the primitive and sacred world nourishing Western exotic dreams. On the other hand, by revisiting the myth of the lost paradise, Hudson conveys the late nineteenth-early twentieth century European perception of the tropical world, a patchwork of Charles Darwin’s theories, Biblical echoes and colonial ideology. Abel surrenders to the influence of the wild, ventures into the weird and entangled forest, seemingly refusing male invasion and domination. Rima’s subsequent death symbolizes the ecological catastrophe brought about by the Europeans in the primitive world of South America: the feathered bird-girl is assimilated to an Edenic being at the mercy of destructive forces. At the same time, Abel’s wish to possess the land reinforces the colonial viewpoint of the narration, while the movement from civilization to the wilderness implies the representation of a Darwinian struggle. Hudson frames the tropical space as substantially ambiguous, attractive and destructive for both colonizers and colonized, and through his narrative he introduces the fear of natural loss in the extreme form of the extinction of the green world.